1993
DOI: 10.1111/j.1558-5646.1993.tb02149.x
|View full text |Cite
|
Sign up to set email alerts
|

THE GENETICS AND COST OF CHEMICAL DEFENSE IN THE TWO-SPOT LADYBIRD (ADALIA BIPUNCTATAL.)

Abstract: Ladybirds (Coccinellidae) defend themselves against attack by vertebrate predators by exuding a fluid from the femero-tibial joints. This fluid carries a noxious or toxic alkaloid. The amount of fluid produced during a single attack can be very high (up to 20% of fresh body weight), and the weight of the self-synthesized alkaloid can amount to several percent of the weight of the fluid. A study was carried out on these two defense characters and two other fitness characters (body weight and growth rate) to dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…Sex-limited G-matrix structure has been noted elsewhere (Holloway et a!., 1993). It is possible that different constraints operate in the two sexes, with energy being used in different ways (Maynard Smith et a!., 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex-limited G-matrix structure has been noted elsewhere (Holloway et a!., 1993). It is possible that different constraints operate in the two sexes, with energy being used in different ways (Maynard Smith et a!., 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In many insect species, however, sexual dimorphism in life history traits, such as emergence body weight or development period, is often very evident. In addition to this, Holloway et al (1993) showed that estimates of additive genetic variation and covariation in and between life history traits differed between the sexes in a population of the two-spot ladybird, Adalia bipunctata. This suggests that each sex may be subject to a different set of constraints that is reflected in the structure of the life history genetics.…”
mentioning
confidence: 99%
“…1-1), which thus serves a dual role in C. septempunctata chemical ecology as an enemy repellent and aggregation pheromone (Al Abassi et al, 1998). The amount of reflex fluid emitted by ladybirds in response to an attack can be very high (up to 20% of fresh body weight), and the weight of the alkaloid can amount to several percent of the weight of the fluid (Holloway et al, 1993). The potential aposematic cues present in the multiple-component defence secretion of C. septempunctata have been investigated in feeding experiments with Japanese quail, Coturnix coturnix japonicus ( Marples et al, 1994).…”
Section: Enemies and Competitorsmentioning
confidence: 99%
“…In the field, larvae often face limited aphid availability (Osawa, 1989;Yasuda and Shinya, 1997;Jansen and Hautier, 2008). In this circumstance, one possible way of avoiding intraguild predation more effectively is by reflex bleeding-based protection (Komai, 1956;Holloway et al, 1991Holloway et al, , 1993.…”
Section: Introductionmentioning
confidence: 99%